2017
DOI: 10.7322/jhgd.124092
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with speech, hearing and language disorders among children in a primary care outpatient center

Abstract: Introduction: Appropriate communication behaviors are developed when the complex language processes are wellbalanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…A Tabela 2 representa os critérios de inclusão e exclusão aplicados especificamente para esta pesquisa. O estudo obteve pontuação 12 no protocolo modificado de Pithon et al 9 para avaliação da qualidade dos mesmos.…”
Section: Critérios De Seleçãounclassified
“…A Tabela 2 representa os critérios de inclusão e exclusão aplicados especificamente para esta pesquisa. O estudo obteve pontuação 12 no protocolo modificado de Pithon et al 9 para avaliação da qualidade dos mesmos.…”
Section: Critérios De Seleçãounclassified
“…For those with speech disorders, the causes were majorly, congenital and stroke related whereas for hearing disorders, it was mostly age, ototoxic drugs, childhood infections etc. [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In the same line of care for infants and children, Goulart et al 8 , evaluated the occurrence of hearing and speech disorders and associated factors in children and reported that the prevalence of speech disorders in the studied children was 22%, and the gender, age or suspected hearing impairment were not associated with the occurrence of speech disorders and/or auditory complaints, and continuous surveillance is necessary at this stage of the child's development.…”
mentioning
confidence: 99%